Antifungal Analysis of Papaya Seed Extracts and Biosynthesized Silver Nanoparticles - Tri Lestari Simangunsong; Ananda Putra; Sahna Ferdinand Ginting; Fiska Maya Wardhani; Hairus Abdullah; Refi Ikhtiari (Science and Technology Indonesia, 2022)
The purpose of research is to investigate the antifungal potential of papaya seed extract and the biosynthesis of silver nanoparticles by C. papaya extract. Here we report 14 secondary metabolites from C. papaya seed extract detected by gas chromatography mass spectroscopy. Bioactive components were majority classified as fatty acid-methyl ester, heterocyclic amides, and phenolic compounds. The proposed mechanisms of those metabolites on inducing antifungal activity were comprehensively studied. We found that the n-hexane fraction was the solely fraction to produce the silver nanoparticles. Scanning electron images presented the aggregation and evenly distribution of spherical silver nanoparticles. The XRD exhibited the crystallization of the bio-organic synthetic phase based on the specific spectrum of 2-theta at 38.9 degree with miller index [1,1,1]. The particle size analyzer also confirmed the nanoscale of synthesized materials as in the average size of 92.1 nm (Z) and 0.406 (PI). Antifungal effects were examined by disc diffusion method upon each fraction with varying concentrations of 25%, 50%, 75%, and 100% (w/w) against C. albicans. ANOVA analysis showed no significant difference among all fractions tested (p > 0.25). The antifungal activity was categorized as a moderate effect with the mean of inhibition zone ranging from 6.1 to 6.8 mm. However, the potential of papaya seed extract is relatively better than the papaya leaves extract, as previously reported. We suggest further studies on the molecular docking of the secondary metabolites against nanoparticle, and specific biomolecular analysis according to the mechanism of action.